Organisational culture and structure as mechanisms for the reduction of human behavioural variability at the Merged Faculty of Education of the University of Kwazulu Natal (UKZN) - Mbele, Zuko (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Philosophy))--University of Stellenbosch, 2008.